Periodical famines Irish memories in transatlantic news media, 1845-1919 - Janssen, Lindsay (Indiana University Press, 2025)
"Long recognized as Ireland's greatest demographic disaster in recent history, the Great Famine of 1845-1851 has shaped Irish identities around the world. From the monuments erected to commemorate its victims to the political rhetoric involving it to the novels, poems, songs, and films that it continues to inspire, the Famine remains a crucial part of Irish memory. Famine memories have also reached across history and national borders to establish links with cultural groups who were not directly connected to the Irish diaspora. Periodical Famines reveals how, within the transatlantic Irish periodical market between 1845 and 1910, Irish, Irish American, and Irish Canadian newspapers and magazines acted as carriers and shapers of cultural identities. Lindsay Janssen argues that famine memory was deployed transhistorically to help represent other crucial events in the Irish past, and periodicals used Famine recollections transnationally to give new meaning to events outside of Ireland, such as labor issues in the United States and the Second Boer War. Moving beyond individual writings to interrogate how different texts printed within a periodical issue influenced each other and affected audiences' attitudes to Irish hunger and distress, Janssen's cotextual approach reveals the intricate and sometimes divergent paths that Famine memory traveled through in the decades during and after its onset. Drawing upon a substantial corpus of creative and nonfiction periodical publications (including nearly 600 works of poetry and prose fiction), Periodical Famines is a thorough analysis of transatlantic Irish periodical culture during and after the Great Famine, demonstrating how periodicals' transmission of famine memories shaped global cultures"--